Activity levels of B-esterases in the tadpoles of 11 species of frogs in the middle Paraná River floodplain: Implication for ecological risk assessment of soybean crops - Lajmanovich, Rafael Carlos (2010)
Soybean fields provide habitats for many species of amphibians. However, the persistence and health of amphibian populations may be at risk from the increasing use of pesticides and other agricultural chemicals. We examined the activities of acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and carboxylesterases (CbEs) in 11 syntopic species of larval anurans. In vitro effects of malaoxon causing 50% BChE inhibition (IC50) were also studied. In addition, we calculated a relative risk index (RI) based on the geographic distributions of the anurans, the phenology of soybean cultivation, and basal enzymatic values related to potential pesticide detoxification. Among the 11 species, AChE activity varied from 17.5±1.6 to 68.2±4.7nmolmin-1mg-1 protein (PT). BChE activity also varied significantly, ranging from 3.3±0.4 to 7.5±0.4nmolmin-1mg-1PT. Both measures of CbE activities varied widely (CbE α-NA: 2.1±0.5-12.4±1.1nmolmin-1mg-1PT; CbE-4NPV: 21.8±1.8-102.6±7.9nmolmin-1mg-1PT). We also corroborate that lower BChE activity levels for the tadpoles were associated at minor IC50 values. The results of this study demonstrate significant variation in enzymatic levels among several tadpole species and intermediate to high RI values for 7 species. Based on these results, it appears that a conversion of native ecosystems to soybean crops may lead to increased ecological risk for anuran amphibians.